2012
DOI: 10.1105/tpc.112.101220
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Plant Protein INAPERTURATE POLLEN1 Marks Distinct Cellular Domains and Controls Formation of Apertures in the Arabidopsis Pollen Exine

Abstract: Pollen grains protect the sperm cells inside them with the help of the unique cell wall, the exine, which exhibits enormous morphological variation across plant taxa, assembling into intricate and diverse species-specific patterns. How this complex extracellular structure is faithfully deposited at precise sites and acquires precise shape within a species is not understood. Here, we describe the isolation and characterization of the novel Arabidopsis thaliana gene INAPERTURATE POLLEN1 (INP1), which is specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(129 citation statements)
references
References 57 publications
7
121
0
Order By: Relevance
“…Our phylogeny supports this hypothesis and suggests that inaperturate pollen of New World genera evolved under two possible scenarios: (i) through two independent transitions in T4 (Bia) and T5 (Acidoton 1 and Platygyna); or (ii) by a single transition in the ancestor of the New World Tragiinae clade followed by a reversal to tricolpate pollen in the core New World Tragiinae (T6-T10). The loss and recovery of pollen apertures seems like a complicated evolutionary hypothesis, but may be plausible if the phenotypic expression of apertures were influenced by a single gene, such as INAPERTURATE POLLEN1 described in Arabidopsis thaliana (Dobritsa and Coerper 2012). Our phylogeny confirms the separate origin of inaperturate pollen in Megistostigma (T2).…”
Section: ] Cardinal-mcteague and Gillespie: Phylogeny Of Plukenetsupporting
confidence: 60%
“…Our phylogeny supports this hypothesis and suggests that inaperturate pollen of New World genera evolved under two possible scenarios: (i) through two independent transitions in T4 (Bia) and T5 (Acidoton 1 and Platygyna); or (ii) by a single transition in the ancestor of the New World Tragiinae clade followed by a reversal to tricolpate pollen in the core New World Tragiinae (T6-T10). The loss and recovery of pollen apertures seems like a complicated evolutionary hypothesis, but may be plausible if the phenotypic expression of apertures were influenced by a single gene, such as INAPERTURATE POLLEN1 described in Arabidopsis thaliana (Dobritsa and Coerper 2012). Our phylogeny confirms the separate origin of inaperturate pollen in Megistostigma (T2).…”
Section: ] Cardinal-mcteague and Gillespie: Phylogeny Of Plukenetsupporting
confidence: 60%
“…4a). A functional copy of INP1 is necessary for fertile pollen development in A. thaliana (Dobritsa and Coerper, 2012). Because the same 8 bp deletion was also found in the female M. rotundifolia (Fig.…”
Section: Fig 1: Dioecy and Hermaphroditism The Morphology Of Flowermentioning
confidence: 63%
“…Like Ramos et al (2014), we propose that females arose via hermaphroditic selfing. INP1 is involved in the formation of pollen surface apertures in Arabidopsis (Dobritsa and Coerper, 2012) and is not functional in females; this could explain the production of sterile unapertured pollen grains in females of dioecious grape species (Caporali et al, 2003;Gallardo et al, 2009). Importantly, these data show that hermaphrodite genotypes do not share the 8 bp deletion in INP1 found in females, differing in pollen fertility, suggesting that INP1 does not participate in pistil fertility.…”
Section: Sex-linked Genes Have Distinct Expression Patterns and Are Hmentioning
confidence: 99%
“…We found that the gene at one limit of the sex locus, annotated as INAPERTURATE ( INP1) 17 , showed a 8-bp deletion in exon2 in all female haplotypes, resulting in a premature stop codon and a truncated protein (Figure 2b). INP1 loss-of-function mutant in A. thaliana lacks pollen apertures 18 , similarly to the pollen of female V. sylvestris 2 . We found that INP1 was highly specific of mature flower buds of V. vinifera , consistent with a role in late pollen development 19 .…”
Section: Figurementioning
confidence: 98%